Experimental study of liquid spreading on pattern surface - Ong, Fu Lin. (2011)
This report documents the research and experimental study on the liquid spreading on a patterned surface made by micro-sized glass balls ranging from 30 to 90 µm. The micro-sized balls are compressed on a polymer using an Instron Mechanical Tester to form a patterned mould. Patterned silicone samples are made by pouring the silicone solution over the patterned polymer mould and forming a mirror image on the silicone. The silicone solution is shaken using ultrasonic bath and cured under room temperature. Dimpled silicone samples are made and used for testing to study how the liquid spreads. The FTA 32 which consists of a high speed camera is used to capture the dynamic process of the liquid spreading.Tests are carried out and repeated for five similar dimpled silicone samples. It is found that the contact angle of the liquid spreading over the samples is consistent throughout and it has a grand average contact angle of 116.93o. A flat silicone is also made by polishing clean a polymer and pouring the silicone solution over it. The dimpled silicone samples are used to conduct a comparison between a patterned surface and a non-patterned surface to study the effects of the different surface roughness on the liquid spreading. It is observed that the flat silicone has a lower contact angle of 80.93o compared to the dimpled samples. This resulted in a better wetting ability and adhesiveness on a flat surface compared to the patterned surface which has a poorer wettability.